2017
DOI: 10.3390/s17030527
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of a Stationary Electrode in a Vertically-Driven MEMS Inertial Switch for Extending Contact Duration

Abstract: A novel micro-electro-mechanical systems (MEMS) inertial microswitch with a flexible contact-enhanced structure to extend the contact duration has been proposed in the present work. In order to investigate the stiffness k of the stationary electrodes, the stationary electrodes with different shapes, thickness h, width b, and length l were designed, analyzed, and simulated using ANSYS software. Both the analytical and the simulated results indicate that the stiffness k increases with thickness h and width b, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The inertial switch was fabricated by UV-LIGA, in which the method of width compensation was adopted to improve the fabrication accuracy. The result showed that the contact time can reach 260 μs when the designed switch is triggered by 32 g. At the same time, Xu et al [87] proposed a vertically driven MEMS inertial switch with a flexible structure. The designed switch can achieve 125 μs contact time at 288 g acceleration.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inertial switch was fabricated by UV-LIGA, in which the method of width compensation was adopted to improve the fabrication accuracy. The result showed that the contact time can reach 260 μs when the designed switch is triggered by 32 g. At the same time, Xu et al [87] proposed a vertically driven MEMS inertial switch with a flexible structure. The designed switch can achieve 125 μs contact time at 288 g acceleration.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
“…The result showed that the contact time can reach 260 μs when the designed switch is triggered by 32 g . At the same time, Xu et al [ 87 ] proposed a vertically driven MEMS inertial switch with a flexible structure. The designed switch can achieve 125 μs contact time at 288 g acceleration.…”
Section: Classification Of Mems Switches Based On Driving Principlmentioning
confidence: 99%
“…The majority of the reported inertial switches have a single acceleration threshold, so that they only provide ON-OFF information [16][17][18][19][20][21][22]. They produce ON signal if the acceleration is higher than the predesignated threshold level and OFF signal otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…MEMS inertial switches are widely applied in many fields, such as military, automobiles, industrial transportation, handled devices, safety, and geriatric healthcare systems due to the advantages of miniaturization, low cost, large volume production, zero power consumption at a normal state, and resistivity to electromagnetic noise [7][8][9][10][11][12][13][14][15][16]. When the inertial switch is accelerated above the threshold value along the sensing direction, the movable electrode moves toward the stationary electrode touching it, which closes an external circuit [17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…A two bits accelerometer has been successfully fabricated and demonstrated in the 0-1g range. Most of the reported inertial switches are inertial switches with one threshold level [9,[11][12][13] and many of these devices are not resettable [32][33][34].…”
mentioning
confidence: 99%